Comparison of cleaning effectiveness of single rotary file OneShape and reciprocating F2 Protaper with Protaper Universal sequence: A SEM analysis - Adish A. Saraf; Anand C. Patil; T.M. Mangala; Rushikesh Mahaparale; Sneha Mali; Sagar Pawar (Elsevier, 2020)
Aim: This in vitro study intend to compare the cleaning effectiveness of Protaper universal sequence with reciprocating F2 Protaper and single rotary file One shape. Materials and method: 30 extracted human 1st mandibular molars were chosen for the analysis. Three NiTi file systems were used for mechanical preparation, ProTaper full sequence in rotary motion, single F2 Protaper file used in reciprocating motion, and One shape single file used in a circular motion. Irrigation was carried out after each instrument use using 5 ml of 5% NaOCl followed by normal saline. The root canal surface was evaluated at three different areas (coronal, middle and apical thirds) using Scanning Electron Microscopy. Debris and the Smear layer were evaluated. Data were analyzed statistically using the Friedman test and Kruskal-Wallis test (p ≤ 0.05). Results: A statistically significant difference (p ≤ 0.05) was observed in the debris score of the Protaper universal group when the 3 thirds of the root were compared. Intergroup comparisons confirmed a statistically significant difference at the coronal and apical third of the roots when debris scores were evaluated. Intragroup comparison for the smear layer demonstrated a statistically significant difference (p ≤ 0.05) at all the 3 levels of the radicular canal for the 3 groups studied. Intergroup comparisons revealed a statistically significant difference (p ≤ 0.05) in the middle and apical 1/3rd when the smear layer was evaluated. Conclusion: The Protaper full sequence group provided better results than Single F2 ProTaper and One shape groups when debris and smear layer removal was investigated.